DETERMINANTS OF FERTILITY PREFERENCE AMONG WOMEN AGED 15-49 YEARS IN CENTRAL JAVA PROVINCE (2022 FAMILY LIFE SURVEY ANALYSIS) - Ardiningsih, Eka Setya; Agushybana, Farid; Shaluhiyah, Zahroh (Jurnal Biometrika dan Kependudukan, 2024)
Uncontrolled population growth is a significant challenge for societies and governments, particularly in the healthcare sector. Indonesia as the world's fourth most populous country, faces this issue with a Total Fertility Rate (TFR) of 2.45, falling short of the intended target of 2.1 for achieving balanced population growth. Furthermore, Central Java Province, one of the most populous regions, records a TFR of 2.27, which is also below the target. It's crucial to note that even a slight decrease in TFR in a populous province can have a significant impact on the national TFR. This research investigates the determinants of fertility preference among women aged 15-49 in Central Java Province, using 2022 Family Life Survey data from the National Population and Family Planning Board 2022. The results of bivariate analysis using the Chi-square test (α=5%) indicate that fertility desires had a significant association with age at first marriage, education, occupation, and health insurance participation, but not related to contraceptive use. Multiple logistic regression (α=5%) reveals that women of reproductive age who married at 21 or older (AOR=0.791; 95% CI:0.786; 0.796) and employed women (AOR=0.798; 95% CI:0.793;0.803) were less likely to desire more than two children. On the other hand, women with health insurance subscriptions were more likely to desire more than two children (AOR=1.129; 95% CI:1.121;1.137). These findings emphasize that promoting women's education and employment, enhancing adolescent reproductive health programs, and aligning healthcare and family planning policies are essential strategies to reshape fertility preferences among women of reproductive age in Indonesia.